Cynomolgus Monkey as a Potential Model to Assess Drug Interactions Involving Hepatic Organic Anion Transporting Polypeptides: In Vitro, In Vivo, and In Vitro-to-In Vivo Extrapolation - Shen, Hong; Yang, Zheng; Mintier, Gabe; Han, Yong-Hae; Chen, Cliff; Balimane, Praveen; Jemal, Mohammed; Zhao, Weiping; Zhang, Renjie; Kallipatti, Sanjith; Selvam, Sabariya; Sukrutharaj, Sunil; et al. (The Journal of pharmacology and experimental therapeutics, 2013)
Organic anion–transporting polypeptides (OATP) 1B1, 1B3, and 2B1 can serve as the loci of drug–drug interactions (DDIs). In the present work, the cynomolgus monkey was evaluated as a potential model for studying OATP-mediated DDIs. Three cynomolgus monkey OATPs (cOATPs), with a high degree of amino acid sequence identity (91.9, 93.5, and 96.6% for OATP1B1, 1B3, and 2B1, respectively) to their human counterparts, were cloned, expressed, and characterized. The cOATPs were stably transfected in human embryonic kidney cells and were functionally similar to the corresponding human OATPs (hOATPs), as evident from the similar uptake rate of typical substrates (estradiol-17β-d-glucuronide, cholecystokinin octapeptide, and estrone-3-sulfate). Moreover, six known hOATP inhibitors exhibited similar IC50 values against cOATPs. To further evaluate the appropriateness of the cynomolgus monkey as a model, a known hOATP substrate [rosuvastatin (RSV)]-inhibitor [rifampicin (RIF)] pair was examined in vitro; the monkey-derived parameters (RSV Km and RIF IC50) were similar (within 3.5-fold) to those obtained with hOATPs and human primary hepatocytes. In vivo, the area under the plasma concentration-time curve of RSV (3 mg/kg, oral) given 1 hour after a single RIF dose (15 mg/kg, oral) was increased 2.9-fold in cynomolgus monkeys, consistent with the value (3.0-fold) reported in humans. A number of in vitro–in vivo extrapolation approaches, considering the fraction of the pathways affected and free versus total inhibitor concentrations, were also explored. It is concluded that the cynomolgus monkey has the potential to serve as a useful model for the assessment of OATP-mediated DDIs in a nonclinical setting.